A meta-analysis of the Masquelet technique and the Ilizarov bone transport method for the treatment of infected bone defects in the lower extremities. (3rd June 2022) - Ren, Cheng; Li, Ming; Ma, Teng; Li, Zhong; Xu, Yibo; Sun, Liang; Lu, Yao; Wang, Qian; Xue, Hanzhong; Zhang, Kun
Purpose: To compare the clinical outcomes of the Masquelet technique and Ilizarov bone transport method for the treatment of patients with infected bone defects in the lower extremities.Methods: Eligible studies were searched from six databases until 12 April 2021. Data extraction was independently conducted by two investigators, which was followed by a quality assessment. Weighted mean difference (WMD) and 95% confidence interval (CI) were used to analyze continuous variables, while odds ratio (OR) and 95% CI were used to analyze categorical variables. All statistical analyses were conducted using RevMan 5.3 and Stata 12.0.Results: Thirteen articles were included in this meta-analysis. There was a significant difference observed in hospitalization costs (WMD [95% CI] = −1.75 [−2.50, −0.99] thousand US dollar, p < 0.00, 001), final union time (WMD [95% CI] = −4.54 [−6.91, −2.17] months, p = 0.0002), time to full weight bearing (WMD [95% CI] = −1.73 [−3.36, −0.10] months, p = 0.04), quality of life (WMD [95% CI] = 7.70 [4.74, 10.67], p < 0.00, 001), and the risk of complications (OR [95%CI] = 0.39 [0.19, 0.79], p = 0.009) between the Masquelet and Ilizarov groups. No significant differences in other outcomes were observed between the two groups.Conclusion: Masquelet technique exhibited the advantages in the lower hospitalization cost, shorter final union time, shorter time to full weight bearing, lower rate of complications, and better post-operative quality of life, compared with Ilizarov bone transport method. However, this finding should be confirmed in large-scale clinical samples.